READER EMPATHY AND LAUGHTER: HOW COMIC VISION FOSTERS CONNECTION ACROSS CULTURES - G. BANAZEER BANU; Dr. S. GUNASEKARAN (The Bioscan, 2025)
This research explores the capacity of comic vision to generate reader empathy across cultural and temporal boundaries through a comparative analysis of selected works by Mark Twain, Stephen Leacock, and R.K. Narayan. Moving beyond humor as mere entertainment, the study investigates how the narrative construction of comedy in these authors fosters a deeper connection with readers by humanizing characters, inviting emotional resonance, and exposing shared social predicaments. Twain’s episodic tales such as Adventures of Huckleberry Finn and The Celebrated Jumping Frog of Calaveras County employ satire and colloquial voice to draw attention to the moral worth and humanity of marginalized figures, notably slaves and rural folk. Leacock’s genial sketches, like those in Sunshine Sketches of a Little Town, present caricatured but affectionate portrayals of small-town Canadian life, celebrating community eccentricities while inviting readers into a shared cultural memory. Narayan’s short stories, particularly from Malgudi Days, derive humor from the ordinariness of Indian life, highlighting character contradictions with subtle irony and warmth. Using affect theory, reader-response criticism, and humor ethics, this paper argues that comic narrative enables empathetic identification by softening boundaries of race, class, and nationality. Through humor, these writers create spaces for ethical reflection, intercultural understanding, and emotional engagement. The analysis reveals how comic form functions not only as a stylistic device but as an ethical and affective bridge, enabling laughter that unites rather than divides. This study contributes to cross-cultural humor studies and affirms comedy’s role in fostering global humanistic dialogue.